Ultrasound assisted synthesis of heterostructured TiO2/ZnFe2O4 and TiO2/ZnFe1.98La0.02O4 systems as tunable photocatalysts for efficient organic pollutants removal. Issue 4 (15th February 2022) - Coromelci, Cristina; Neamtu, Mariana; Ignat, Maria; Samoila, Petrisor; Zaltariov, Mirela Fernanda; Palamaru, Mircea
Abstract: As a response to the everyday growing concern about wastewater treatment, some new mesoporous TiO2 /ZnFe2 O4 and TiO2 /ZnFe1.98 La0.02 O4 catalysts were synthesized during this research. The ultrasound template-assisted sol-gel method was employed in the synthesis, using conventional calcination and microwave treatment for pore directing agent removal. The as-prepared samples were characterized from the structural, optical, morphological and textural points of view, confirming the presence of spinel ferrites and TiO2 anatase crystals in the nanocomposites. The synthetized powders exhibit promising characteristics for their use in adsorption and light activated degradation of organic pollutants. The photodegradation experiments of model pollutant basic blue 9 (methylene blue) dye were performed at laboratory scale and the optimum experimental parameters were determined as 0.4 g/L catalyst and 30 mg/L initial dye concentration, under UV light irradiation, visible irradiation and natural sun light irradiation. The conventionally calcined lanthanum doped TiO2 /ZnFe1.98 La0.02 O4 system exhibited the highest efficiencies of 97%, 70% and 91% for dye removal from the solution, under UV light, visible light and natural sun light irradiation, respectively. Moreover, the catalytic activity was similar for up to four consecutive cycles. A lower yield of organic pollutant removal was observed in wastewater treatment plant (WWTP) effluent. The obtained results show that the newly synthesized catalysts are good candidates for the removal of water pollutants through adsorption and photocatalysis. Graphical abstract: Image 1